Advanced Additive Manufacturing - Shishkovsky, Igor V. (IntechOpen, 2022)
Additive manufacturing (AM) is now being used to produce series components for the most demanding applications. It is a disruptive, if not revolutionary, manufacturing technology. The biggest advantage of this technology is its capacity to make parts with any free form, thus paving the way for free and complex part design. Components and integrated structures with complex designs that would not have been possible just a few years ago can now be made according to various requirements. The net-shape manufacturing capacity of AM allows a considerable saving of materials, conventional thermomechanical processing, and machining processes, making it an environmentally friendly manufacturing technology. This book includes two sections that cover new approaches in AM for biomedical applications and advanced technological solutions.